PENGEMBANGAN ES KRIM JAGUNG DAN SUSU JAGUNG SEBAGAI PRODUK UNGGULAN DESA KALIGUNTING KECAMATAN MEJAYAN KABUPATEN MADIUN JAWA TIMUR - Ulya Sarofa; Luqman Agung Wicaksono (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Kaligunting Village was known for its rich natural wealth. One of the commodities that is preferred in the natural richness of the village is sweet corn. The utilization of this sweet corn harvest is not maximized because it is still limited to the sale of crops on brokers and traditional processed products. Therefore, it is necessary to implement the Community Service Program RISMA (“Hibah Penerapan Hasil Riset Bagi Masyarakat” or grant implementation research for the community) based on the innovation of products processed corn as the flagship commodity in Kaligunting, one of them by making the processed products has a higher economic value and is attractive to be marketed in the form of milk and corn ice cream. The purpose of this community service program was to transfer the appropriate technology to the processing of sweet corn into processed products (corn milk and corn ice cream) that has a higher economic value so as to increase the value of sweet corn, Extend shelf life, and potentially contribute to the community. Methods are done through a passive approach with survey site activities and potential villages, training either theory or practice, monitoring and evaluation, and marketing preparation. The results of monitoring and evaluation show participants capable of processing corn into corn ice cream and corn milk with packaging and labelling, in addition participants are able to develop the basic science that has been gained to make products based other local food, such as brem ice cream.